Investigation of the Microstructure and Mechanical Performance of GH4099 Alloy Fabricated by Selective Laser Melting - Chen, Bo; Zhong, Yilong; Li, Wenying; Li, Yanying; Wang, Qiyou; Lu, Yingjie; Qi, Zichen; Wang, Shenqi; Li, Yanbiao (Materials, 2025)
GH4099 is a nickel-based, high-temperature, precipitation-strengthened alloy with excellent mechanical properties and corrosion resistance, widely used in aerospace components. The performance of parts produced by additive manufacturing depends significantly on alloy powder quality and heat treatment. In this study, GH4099 alloy powder was prepared using the EIGA method, and its morphology, particle size distribution, and flowability were analyzed. The mechanical properties and microstructure of parts before and after solution-aging treatment were compared. Results showed that the powder had good sphericity and flowability, with a median diameter D50 of 28.88 μm. The formed parts underwent solution treatment at 1140 °C for 2 h followed by aging at 850 °C for 8 h. After heat treatment, the transverse tensile strength increased to 1122.11 MPa (+15.1%) and the yield strength to 866.56 MPa (+22.3%), while the longitudinal tensile strength reached 1116.81 MPa (+29.4%) and the yield strength 831.61 MPa (+35.2%). This improvement is attributed to the precipitation of γ′ phase. Fractographic analysis revealed a mixed fracture mode characterized by ductile dimples and cleavage facets, indicating that the alloy exhibits favorable toughness-related features under mechanical loading. These findings demonstrate the excellent microstructure and mechanical performance of GH4099 alloy in AM applications, providing a basis for its further use in high-performance aerospace components.